Investigations of nitrogen oxide plasmas: fundamental chemistry and surface reactivity and Monitoring student perceptions in a general chemistry recitation - Blechle, Joshua M., author; Fisher, Ellen R., advisor; Levinger, Nancy E., committee member; Henry, Charles S., committee member; Weinberger, Christopher R., committee member (Colorado State University. Libraries, 2016)
Part I of this dissertation focuses on investigations of nitrogen oxide plasma systems. With increasing concerns over the environmental presence of NxOy species, there is growing interest in utilizing plasma-assisted conversion techniques. Advances, however, have been limited because of the lack of knowledge regarding the fundamental chemistry of these plasma systems. Understanding the kinetics and thermodynamics of processes in these systems is vital to realizing their potential in a range of applications. Unraveling the complex chemical nature of these systems, however, presents numerous challenges. As such, this work serves as a foundational step in the diagnostics and assessment of these NxOy plasmas. The partitioning of energy within the plasma system is essential to unraveling these complications as it provides insight into both gas and surface reactivity. To obtain this information, techniques such as optical emission spectroscopy (OES), broadband absorption spectroscopy (BAS), and laser induced fluorescence (LIF) were utilized to determine species energetics (vibrational, rotational, translational temperatures). These temperature data provide mechanistic insight and establish the relationships between system parameters and energetic outcomes. Additionally, these data are also correlated to surface reactivity data collected with the Imaging of Radicals Interacting with Surfaces (IRIS) technique. IRIS data demonstrate the relationship between internal temperatures of radicals and their observed surface scatter coefficients (S), the latter of which is directly related to surface reactivity (R) [R = 1-S]. Furthermore, time-resolved (TR) spectroscopic techniques, specifically TR-OES, revealed kinetic trends in NO and N2 formation from a range of precursors (NO, N2O, N2/O2). By examining the rate constants associated with the generation and destruction of various plasma species we can investigate possible mechanistic implications. All told, such data provides unparalleled insight into the chemistry of these plasma systems. Part II of this work is focused on understanding the efficacy of a general chemistry recitation program. Such programs can be an valuable tool for improving students’ problem solving skills and understanding using methods that are difficult to implement in large lecture settings. Here, general chemistry students at Colorado State University participated in a variety of recitation activities throughout the first semester of a 2-semester general chemistry sequence, including peer-led exercises, games, and scaffolded worksheets. Through weekly surveys, students were asked to evaluate and assess recitation activities for both interest and effectiveness as part of their course homework. Also included in these survey assignments were content questions relevant to the weekly themes, providing a measure of student learning of recitation topics. Student opinions were correlated with content retention, and these data were compared against student responses to a pre-survey administered before the first recitation session. This analysis allows for monitoring students’ expectations of recitation courses and how well those expectations are met through the various types of activities employed. Ultimately, this work has found that students have positive feeling with respect to individual assignments, but that perspectives on chemistry and the course in general decrease dramatically from the beginning to the end of the semester. Thus, this work can serve as a significant starting points for future efforts to monitor and record student perceptions in the general chemistry recitation classroom, leading to further investigation into the source of changing attitudes and the role that week-to-week activities have on global course attitudes.
Fundamental chemistry and surface reactivity
Monitoring student perceptions in a general chemistry recitation
Keywords: general chemistry recitation; plasma diagnostics; gas-surface reactivity; student attitudes; nitrogen oxide plasmas